Approximation to the Finite Sample Distribution for Nonstable First Order Stochastic Difference Equations - Satchell, S. E. (Econometrica, 1984)
[This paper considers approximations to the distribution of the least squares estimator of α in the model @y"t = @a@y"t"-"1 + @u"t where the @u"t are independently distributed N(0, @s extasciicircum2) and @y"0 is fixed. An Edgeworth approximation for this case is calculated, and compared with results for the stationary case. For extbar@a extbar extgreater 1 and fixed @y"0, the asymptotic distribution is found in closed form; when extbar@a extbar extgreater 1 and @y"0 = 0, an Edgeworth-type approximation is again calculated; this is compared with exact results.]